Entropy and flame transfer function analysis of a hydrogen-fueled diffusion flame in a longitudinal combustor. (1st March 2020) - Sun, Yuze; Zhao, Dan; Ni, Siliang; David, Tim; Zhang, Yang
Abstract: In this work, entropy generation and flame transfer function investigations are conducted on a hydrogen-burnt diffusion flame in a longitudinal combustor with acoustic waves present. For this, a time-domain 2D numerical model of a jet diffusion flame is developed to gain insights on its dynamic response to acoustic disturbances at either resonant or non-resonant frequencies. The model is validated first by comparing the numerical results such as turbulence intensities, pressure and velocity mode shape and flame shapes with the experimental data available in the literature. The model is then applied to evaluate the effects of the frequencies and amplitudes of the forcing acoustic waves, and the flame-holder/nozzle axial positions on entropy generation of both hydrogen- and propane-fueled flames. It is found that the entropy generation rate is sensitive to acoustic forcing frequencies, amplitudes and the nozzle axial positons. Furthermore, entropy produced from the heat conduction and the chemical reaction processes is shown to be dominant and secondary respectively. However, the mass diffusion is found to play a negligible role on the entropy generation. As the acoustic forcing frequency is set to 385 Hz near resonance, the total entropy generation rates are minimized, and the mass diffusion contribution is maximized with the flame being placed at velocity node locations in comparison with other flame-holding locations. Finally, flame transfer function (FTF) analysis is performed by using two different methods. It is shown that the flame responds strongly to low-frequency acoustic disturbances, acting like a band-pass filter. Increasing the acoustic intensity leads to the flame being more sensitive to the acoustic disturbances over more frequency bands. Highlights: Entropy generation of hydrogen-fueled flame in a longitudinal combustor with acoustic waves is studied. Effects of fuel, acoustic frequencies, amplitudes and nozzle positions are examined. Heat conduction and chemical reaction processes are found to play dominant and secondary roles on entropy generation. Flame transfer functions are determined with different intensity of acoustic disturbances. Flame is observed to respond strongly to low-frequency disturbances and acts as a band-pass filter.